ANALISIS RASIO KEMANDIRIAN DAN EFEKTIFITAS KEUANGAN DAERAH DI KABUPATEN BERAU: ANALISIS RASIO KEMANDIRIAN DAN EFEKTIFITAS KEUANGAN DAERAH DI KABUPATEN BERAU - Merlin, Merlin (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
The purpose of this study was to determine the level of independence ratio and regional financial effectiveness in Berau Regency. The method used is a quantitative method or data obtained in the form of numbers. The results showed that from 2017 to 2021 an average of 10.33% was obtained. This shows that the local government of Berau Regency is still in the very low category. The ratio of regional financial effectiveness in Berau Regency in 2017-2021 shows an average percentage of 111.62%. this shows that the local government of Berau district is in the very effective category.